Parents’ Perceptions of Their Children’s Vocational Tracking - Zamir, Sara (Pedagogika, 2023)
Since the establishment of the State of Israel, the country’s high schools have been divided into two main tracks: the academic track that maintains relatively high academic standard and the vocational track. The aim of the research was to study parents‘ perceptions of the vocational education that their children had received. The most prominent finding was that vocational education is not parents’ first or natural choice but a default option.